COMMON NUTRITIONAL DEFICIENCIES IN CHILDREN OF SCHOOL AGE - Sadirkhodjayeva Nilufar Saydullakhodjayevna (Modern American Journals, 2025)
The topic article explores the essential nutrients often lacking in the diets of children between the ages of 6 and 12. This age group is especially vulnerable due to rapid growth, increased physical activity, and the transition to school environments that may not always provide balanced meals. The annotation focuses on key deficiencies such as iron, which can lead to anemia and affect cognitive performance; vitamin D, critical for bone development; calcium, essential for skeletal growth; and iodine, necessary for proper thyroid function and mental development. It also considers the causes of these deficiencies, including poor dietary habits, lack of nutritional education, food insecurity, and cultural or socioeconomic factors. The topic emphasizes the importance of early intervention through dietary improvements, school-based nutrition programs, supplementation when necessary, and awareness among parents, caregivers, and educators. Addressing these deficiencies is crucial to support children's physical health, academic performance, and overall well-being.
Keywords: Schoolchildren, violations in nutrition organization, nutritional status.